2014
DOI: 10.4028/www.scientific.net/msf.775-776.493
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Efficiency of Surface Treatment of Bentonite Clay for Application in Polymeric Membranes

Abstract: The bentonite clay fillers are mostly used for the development of nanocomposites, due to having characteristics which provide to obtain in nanometric particles. The bentonite clay was treated with an ammonium quaternary salt to modify it to organophilic clay. The polymeric membranes and nanocomposites were prepared using the phase inversion technique. The bentonite and organophilic clays were characterized by X-ray fluorescence (XRF), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
1
3
0
5
Order By: Relevance
“…Polyamides are semicrystalline polymers and the presence of peak broadening indicates the existence of amorphous regions. Furthermore, the introduction of clay, regardless of the amount, changes slightly the shape and intensity of the peaks at 20º and 24º of the polyamide6 [30][31][32][33][34][35] . It was found that the addition of 5% w/w of MMT in PA6, cause the appearance of the new reflection at 2θ = From Figure 2, it is noted that the general profile of FTIR spectra of the PA6 remained virtually unchanged, except for a small increase in the intensity of the peaks at wavelengths of 800, 1033 and 1095 cm -1 .…”
Section: Water Permeability and Oil Retentionmentioning
confidence: 99%
“…Polyamides are semicrystalline polymers and the presence of peak broadening indicates the existence of amorphous regions. Furthermore, the introduction of clay, regardless of the amount, changes slightly the shape and intensity of the peaks at 20º and 24º of the polyamide6 [30][31][32][33][34][35] . It was found that the addition of 5% w/w of MMT in PA6, cause the appearance of the new reflection at 2θ = From Figure 2, it is noted that the general profile of FTIR spectra of the PA6 remained virtually unchanged, except for a small increase in the intensity of the peaks at wavelengths of 800, 1033 and 1095 cm -1 .…”
Section: Water Permeability and Oil Retentionmentioning
confidence: 99%
“…A poliamida 6 é um polímero semicristalino e o alargamento dos picos indica a existência de regiões amorfas. Como pode ser observada, a introdução da argila, independente do percentual, altera um pouco o formato e a intensidade dos picos característicos da cristalinidade da poliamida 6 na faixa de aproximadamente 20º e 24º [23,24].…”
Section: Figuraunclassified
“…Analisando a PA6 pura e seus híbridos, foi possível observar que a fase cristalina predominante é a alfa [24][25][26]29]. Além disso, foi constatada nas membranas com 3% e 5% de argila, a presença de um pico em aproximadamente 27°, referente ao elemento quartzo da argila.…”
Section: Figuraunclassified
See 2 more Smart Citations